2021
DOI: 10.1186/s13059-020-02231-9
|View full text |Cite
|
Sign up to set email alerts
|

SpRY greatly expands the genome editing scope in rice with highly flexible PAM recognition

Abstract: Background Plant genome engineering mediated by various CRISPR-based tools requires specific protospacer adjacent motifs (PAMs), such as the well-performed NGG, NG, and NNG, to initiate target recognition, which notably restricts the editable range of the plant genome. Results In this study, we thoroughly investigate the nuclease activity and the PAM preference of two structurally engineered SpCas9 variants, SpG and SpRY, in transgenic rice. Our st… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
64
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(66 citation statements)
references
References 42 publications
2
64
0
Order By: Relevance
“…Very recently, three papers were published describing TadA8e fused with different Cas9 variants, including SpRY, SpG, SpCas9‐NRRH, SpCas9‐NRTH and SpCas9‐NRCH for A‐to‐G base editing (Li et al, 2020; Ren et al, 2021; Xu et al, 2021). In agreement with our results, TadA8e showed high editing efficiencies in these different systems, especially when fused with SpG, SpCas9‐NRRH, SpCas9‐NRTH, and SpCas9‐NRCH, and its homozygous substitution rate was as high as 66.7% for a specific target (Li et al, 2020).…”
Section: Resultsmentioning
confidence: 99%
“…Very recently, three papers were published describing TadA8e fused with different Cas9 variants, including SpRY, SpG, SpCas9‐NRRH, SpCas9‐NRTH and SpCas9‐NRCH for A‐to‐G base editing (Li et al, 2020; Ren et al, 2021; Xu et al, 2021). In agreement with our results, TadA8e showed high editing efficiencies in these different systems, especially when fused with SpG, SpCas9‐NRRH, SpCas9‐NRTH, and SpCas9‐NRCH, and its homozygous substitution rate was as high as 66.7% for a specific target (Li et al, 2020).…”
Section: Resultsmentioning
confidence: 99%
“…Among engineered Cas9 variants, the near-PAMless nucleases, SpG and especially SpRY variants, present the most relaxed PAM requirements to date. The activity of these nucleases has been well described in human cell lines 6 and more recently in plants [33][34][35][36] . However, SpG and SpRY have never been applied in animals.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, recent publications have demonstrated not only the capacity of SpG and SpRY to produce indels in mammalian cells and plants and but also their adaptation to base editor systems that take advantage of their relaxed PAMs 6,34,35 . Our optimized CRISPR-SpG and SpRY systems in vivo now set the basis for carrying out base editing and other CRISPR applications in animals [40][41][42] with a greatly improved targeting landscape.…”
Section: Discussionmentioning
confidence: 99%
“…The researchers further optimized SpG to develop SpRY that has the potential of targeting almost all PAM. Xu et al (2020a) have researched the effectiveness of both SpG and SpRY nucleases against separate PAMs and their use in both cytosine and adenine base editing using transgenic rice callus. They reported that even though SpG recognizes NG PAM sequences, its performance is less when compared to SpCas9-NG in rice.…”
Section: Currently Available Types Of Base Editorsmentioning
confidence: 99%